"To go or not to go?": business travel decision with the risk of COVID-19. Issue 8 (3rd August 2022) - Lin, Eliver; Law, Colin; Tan, Seck
ABSTRACT: COVID-19 have led companies and organizations to carefully decide overseas business travel after borders reopen. This study aims to develop a theory to guide a structural analysis of the situational factors that companies and organizations would consider in overseas business travel decisions and how to measure these factors. A qualitative research approach was adopted. Bunn's situational characteristics were used as the starting point to guide the study. The findings suggest that the decision results from a struggle between carry-on and hold-back forces, which were affected by two and six situational factors respectively. Their measuring dimensions and ten propositions are suggested.